Enhanced anti-tumor activity by adenovirus mediated LIF and IL-24 co-expression on glioma cells and its mechanism - Zhao, Yaodong; Wei, Zilong; Yin, Jia; Zhang, Quanbin; Shan, Yunbo; Sheng, Weihua; Yang, Jicheng (European Journal of Oncology and Environmental Health, 2014)
Objective: Gene therapy on the glioma has been studied for many years, but most studies still remain at the level of single gene therapy. However, the glioma is characterized by a multistep process of genetic and molecular changes to oncogenes and tumor suppressor genes, which limits the efficacy of single gene-mediated therapy due to the difficulty of finding a pivotal gene conferring its occurrence in glioma gene therapy. In this paper, we try to study the anti-tumor effects and mechanism of a recombinant adenoviral vector co-expressing leukemia inhibitory factor (LIF) and interleukin-24 (IL-24) on glioma cells. Materials and Methods: LIF/IL-24 bicistronic adenovirus (Ad-LIF-IL-24) was constructed and preserved by our laboratory. The enhanced growth-suppressing and apoptosis-inducing effect of Ad-LIF-IL-24 on the U251 glioma cells in vitro was assessed, and the expressions of the apoptosis-related genes (bcl-2, bax, and ICE) were determined. Results: Ad-LIF-IL-24 could induce much more cellular apoptosis of U251 glioma cells than either Ad-LIF or Ad-IL-24 alone at the same virus titer. Molecularly, Ad-LIF-IL-24 could significantly enhance the expressions of bax and ICE though it inhibits the expression of bcl-2. Conclusion: Cancer gene therapy combining LIF and IL-24 may constitute a novel and more effective therapeutic strategy for gliomas, with good potential prospects of clinical application.